The Storm Pony - "Clover, Peter" (London; Young Corgi, 2000)
Every day, Heather's grandfather signals her from the old lighthouse where he lives. But when a wild storm strikes, and there is no signal, Heather knows something must be wrong. There is only one way to reach her grandfather. She must saddle up her fiery pony, Caspar, and ride like the wind. Aimed at age 6-9
Keywords: Grandfathers Juvenile fiction